RANCANG BANGUN DIGITAL LEARNING SYSTEM (DLS) BERBASIS GAMIFIKASI MENGGUNAKAN METODE GAME DEVELOPMENT LIFE CYCLE (GDLC) - Putra, Rocky Ardiansyah Yudistira; Mashuri, Chamdan (FORMAT, 2024)
Digital education is one of the important components in the implementation of the Independent Curriculum in Indonesia. However, the main challenge arises when elementary school students tend to spend more time playing than studying. To overcome this, the development of a gamification-based Digital Learning System (DLS) can be an effective solution. DLS allows students to learn independently and interactively with the support of digital technology, while gamification offers game elements that make the learning process more interesting and enjoyable. In English learning, gamification-based DLS helps students develop vocabulary, grammar, and communication skills in a fun and structured way. Through the application of challenges, rewards, and levels, students are invited to be actively involved in learning, increasing their motivation and learning outcomes. This DLS is not only relevant to the needs of elementary school children who like games, but also supports the achievement of the objectives of the Independent Curriculum, which focuses on flexibility and contextualization of education. This abstract highlights the importance of gamification-based DLS as an interesting and effective English learning innovation for elementary school students in the digital era.